the distance formula is d=sqroot of ((y2-y1)^2 + (x2-x1)^2), so you take -2-(-5) and get -2+5 which is 3, square that you get 9, then you take 4-6 which is 2, square that and you get 4, so then you take 9+4=13, and that all took place under teh radical so the asnwer is the square root of 13
2006-09-18 13:40:54
·
answer #1
·
answered by Ugs 2
·
1⤊
0⤋
Sometimes it helps to draw a picture first. By drawing a picture and connecting the points, you can make a right triangle to help you find your answer.
By taking the absolute value of the distance of the x values (6-4=2), and the same for the y values (-5-(-2))=3), you get two of the sides of the triangle, 2 and 3. Because this is a right triangle, you can use the pythagorean theorem (a²+b²=c²).
So, 3²+2²=c²
9+4=c²
13=c²
â13 = c
2006-09-18 20:47:40
·
answer #2
·
answered by Kayla 3
·
0⤊
0⤋
To do this, subtract the two x-coordinates and square the difference; do the same for y; add these, then do the square root. Here you get:
(6-4)^2 + (-5 - -2)^2 which is 2^2 + (-3)^2 or 4+9 or 13. So sqrt(13) is the distance.
By the way, what you did wrong was to ADD the two coordinates, not SUBTRACT them.
2006-09-18 20:42:14
·
answer #3
·
answered by hayharbr 7
·
1⤊
0⤋
Using the Pythagorean Theorem, which is what the distance formula dresses up as:
a^2 + b^2 =c^2
The side along the horizontal is 2 units (6 - 4 =2), and the side on the vertical is 3 units (|-5 - -2 |= |-5 + 2| = |-3| = 3.
2^2 + 3^2 = c^2
4 + 9 = c^2
13 = c^2
c = sqrt(13)
2006-09-18 20:42:49
·
answer #4
·
answered by powhound 7
·
0⤊
0⤋
change in x = 4 - 6 = -2
change in y = -2 - -5 = 3
x^2 + y^2 = d^2
2^2 + 3^2 = d^2
4 + 9 = d^2
d = sqrt(13)
2006-09-18 20:40:03
·
answer #5
·
answered by J G 4
·
1⤊
0⤋
Îx = 4-6 = -2
Îy = (-2)-(-5) = 3
distance = â((-2)²+(3)²) = â(4+9) = â13
I completely fail to see how you could have gotten 149.
2006-09-18 20:41:18
·
answer #6
·
answered by Pascal 7
·
0⤊
1⤋
D = sqrt((x2 - x1)^2 + (y2 - y1)^2)
(6,-5) and (4,-2)
D = sqrt((4 - 6)^2 + (-2 - (-5))^2)
D = sqrt((-2)^2 + 3^2)
D = sqrt(4 + 9)
D = sqrt(13)
2006-09-19 01:30:56
·
answer #7
·
answered by Sherman81 6
·
0⤊
0⤋
Wrong, the square root of 13 is correct.
2006-09-18 20:54:19
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
d = sqrt((6-4)^2 + (-5-(-2))^2)
d = sqrt(2^2 + (-3)^2)
d = sqrt(4 + 9)
d = sqrt(13)
2006-09-18 20:44:38
·
answer #9
·
answered by DidacticRogue 5
·
0⤊
0⤋